To solve the quadratic equation 3x^2 - 7x - 6 = 0 using the quadratic formula, we first identify the values of a, b, and c:
a = 3
b = -7
c = -6
The quadratic formula states that the solutions for the equation ax^2 + bx + c = 0 are given by:
x = (-b ± √(b^2 - 4ac)) / 2a
Plugging in the values for a, b, and c:
x = (7 ± √((-7)^2 - 4*3*(-6))) / 2*3
x = (7 ± √(49 + 72)) / 6
x = (7 ± √121) / 6
x = (7 ± 11) / 6
Therefore, the solutions are:
x = (7 + 11) / 6 = 18 / 6 = 3
x = (7 - 11) / 6 = -4 / 6 = -2/3
So, the correct answer is x = 3, x = -2/3.
Question Solve the quadratic equation 3x2−7x−6=0 using the quadratic formula. **REMEMBER TO CHECK YOUR SIGNS*** (1 point) Responses x=2/3, x =3 x=2/3, x =3 x=-2/3, x =3 x=-2/3, x =3 x=-2/3, x =-3 x=-2/3, x =-3 x=2/3, x =-3
1 answer